Determinação de constituintes inorgânicos em amostras de ervas e raízes medicinais por espectrometria de absorção atômica com chama - Rafaela Marques Pereira (2010)
It was evaluated in this work sample pretreatment procedures for teaherbal of high national consumption as basil, arnica, boldo, chamomile, lemon grass, green tea, holy thorn, break stone and ginger. It was investigated two types of each plant (A and B), except for ginger. Mild, fast and cheap procedures using water infusion, dilute acid solution and simulated gastric juice were evaluated and compared with a microwave-assisted acid digestion procedure using closed vessels. Analytes quantification (Al, Cu, Fe, Mn and Zn) were performed by flame atomic absorption spectrometry - FAAS. The total content of analytes obtained after total digestion was used to evaluate the efficiency of the extraction procedures. Tea infusion was preparead in a conventional way and homemade microwave oven. Particle size influence on elements extraction was examined in the infusion, as well as in the successiveinfusions. Metal-silica interaction was studied using 4.5 mol L-1 HF solution and elements bioavailability in the digestive tract through the simulation of gastric juice. Total contents were different for herbs and types, but similar values were found for Cu in the A and B medicinal herbs. Iron presented the highest concentration in 82% of the samples. However, in percentage, it was the element less extracted in the infusion. Manganese presented the highest concentration in all infusions, except for green tea. This aspect can demonstrate the weak metal interaction with the organic matrix. Statistical analysis by Pearson's test showed the interaction in the total concentrations of Cu and Zn. Principal component analysis (PCA) and hierarchical clustering analysis (HCA) for the data obtained after microwave-assisted sample digestion procedure andtea infusion in the domestic microwave showed groups according to element composition similarities. The infusion using particle size <63 µm presented high percent values when the procedure was developed in the domestic microwave, because the efficiency of microwave radiation compared to traditional conductive heating. The first successive infusion was the most significant in the elements extraction and Mn was the only element to be measured until the sixth and final infusion. The gastric juice simulation presented values higher than infusion. HF extraction increased the percentage of all elements, compared to infusion and gastric juice simulation, except for Zn in ginger herb extracted withgastric juice simulation. In the HF extraction procedure, the highest extraction percent values were observed for Fe, indicating the strong interaction of this element with the silica sample. Extraction efficiency of the procedures was: diluted HF> simulated gastric juice> infusion. The study provided information that can be used as nutritional and toxicological profiles of the tea herbs investigated.